Halstead-Reitan Deficit Scores in Assessment of Nonimpact Head Injury. Issue 2 (4th March 2017) - Sweeney, James Ernest; Johnson, Andrew M.; Slade, Anne M.
ABSTRACT: Comparisons were made between neuropsychological deficit scores generated by the Reitan-Wolfson system of interpretation (1993) and the computerized Revised Comprehensive Norms for an Expanded Halstead-Reitan Battery (Heaton, Miller, Taylor, Grant, & PAR Staff, 2005 ). The scores were obtained from seat-belted litigants and insurance claimants subjected to extreme physical forces in motor vehicle accidents. Subjects had not sustained direct impact to the head but met criteria for mild traumatic brain injury. The word "nonimpact" has been used to describe this form of head injury. Consistent with previous studies, the Reitan-Wolfson system generated deficit scores suggestive of a greater degree of impairment than the Revised Comprehensive Norms. Demographic characteristics of the normative data used in each interpretive system and the operational definition of impairment were scrutinized. Likely or possible determinants of deficit score discrepancies were identified. On the basis of this information, a method of using the two interpretive procedures in an integrated manner to assess nonimpact head injury was suggested.